Effect of Cr content on interdiffusion and Kirkendall pore formation during homogenization of pack-aluminized Ni and Ni-Cr wires. (October 2018) - Paz y Puente, A.E.; Dunand, D.C.
Abstract: Using both ex situ metallographic imaging and in situ X-ray tomographic microscopy, we investigate the kinetics of Al- and Ni-interdiffusion during homogenization at 825–1100 °C for surface-aluminized, 50 μm diameter Ni wires with 0, 10 or 20 wt%Cr. Kirkendall pores, which are created due to imbalanced diffusion of atomic species, are not observed at any of the homogenization temperatures in the Cr-free Ni-Al wires, which equilibrate to Ni-rich β-NiAl. By contrast, during homogenization of the aluminized Ni-10Cr and Ni-20Cr wires to β-NiAl(Cr) at 1000 and 1100 °C, numerous Kirkendall pores are created within the wire volume, indicating that the addition of Cr significantly increases the imbalance between the Ni and Al diffusivities. These pores eventually coalesce into a single cavity, with crescent-shape cross-sections and high aspect ratio aligned with the axis of the wires, so that a tubular β-NiAl(Cr) structure is formed. Tomography shows that the Ni-rich β-NiAl(Cr) reaction layer grows radially within the Ni-10Cr and Ni-20Cr wires annealed in situ at 825, 900, and 1000 °C according to a parabolic law. The growth kinetics of this layer increase slightly with increasing Cr content and obey an Arrhenius relationship, from which an activation energy of ∼200 kJ/mol is calculated, in good agreement with literature values for interdiffusion in binary NiAl. The two methods, ex situ metallography and in situ X-ray tomography, are complementary. While tomography very rapidly acquires numerous cross-sectional images showing phase contrast on a single wire, thus replacing interrupted annealing and destructive imaging of multiple samples, metallography has higher spatial resolution and can identify additional phases. In the present case, metallography revealed that α-Cr precipitates form during homogenization of the aluminized Ni-Cr wires due to the limited solubility of Cr in β-NiAl; upon full homogenization, these precipitates re-dissolved in the aluminized Ni-10Cr wires, but remained stable in the Ni-20Cr wires. Highlights: Pack cementation was used to deposit Al onto Ni and Ni-Cr wires. Due to radial symmetry and spatial confinement, internal Kirkendall pores form upon homogenization to form a microtube. With increased Cr content in the Ni wire, the central Kirkendall pore is larger indicating that Cr significantly increase DNi/DAl.